The effects of job crafting on tour leaders' work engagement: the mediating role of person-job fit and meaningfulness of work. Issue 5 (8th February 2022) - Guo, Yongrui; Hou, Xinyi
Abstract : Purpose: This study aims to examine the effects of job crafting on the work engagement of tour leaders mediated by person-job fit and the meaningfulness of work. Design/methodology/approach: Derived from a sample of 331 tour leaders in China, the data for this research were analyzed using partial least squares structural equation modeling. Findings: The findings revealed that job crafting increased tour leaders' person-job fit and meaningfulness of work, which stimulated their work engagement. Tour leaders' person-job fit also increased their work engagement and perceptions of the meaningfulness of work. Enhancing the work meaningfulness of tour leaders can significantly increase their work engagement. Person-job fit and meaningfulness of work had a significant mediating effect between job crafting and tour leaders' work engagement. Practical implications: Managers need to provide external conditions for tour leaders' job crafting by expanding structural and social job resources and by creating more stimulating job environments. Managers can enhance tour leaders' work engagement by shaping their work meaning and person-job fit. Originality/value: First, this study empirically tested the effects of job crafting on tour leaders' work engagement, thus directly addressed the lack of academic attention paid to this topic. Second, this study examines the mediating role of person-job fit and meaningfulness of work, with regard to tour leaders' job crafting and work engagement, based on an integrative concept model.